MANAJEMEN MUTU DI PENDIDIKAN ISLAM: STUDI PUSTAKA TENTANG KONSEP DAN IMPLEMENTASI - Ahmad Shuwaifi; Noor Amirudin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Quality management in Islamic education presents significant challenges and opportunities in the face of globalization. This study aims to explore the concept and implementation of quality management in Islamic education through a literature review. The study employs a descriptive-analytical approach by analyzing secondary data from relevant literature. The findings indicate that the application of quality management principles based on Islamic values, such as Panca Jiwa and Sharia principles, can enhance the quality of education in Islamic institutions. Additionally, strategies such as Total Quality Management and the integration of Islamic values into the curriculum strengthen institutional competitiveness. However, the study also identifies significant challenges, including resistance to change, limited funding, and the need for technological adaptation. The study concludes that Islamic education requires a balanced quality management approach that aligns religious values with the demands of globalization. This study provides theoretical contributions to developing a quality management system that is relevant to the needs of the modern era.